Secondary Trigeminal Neuralgia Caused by Cerebellopontine Angle Arachnoid Cyst in A 27-Year-Old Female: A Case Report - I Wayan Niryana; Marthinson Andrew Tombeng; Christopher Lauren; Sri Maliawan; Nyoman Golden; Tjokorda Gde Bagus Mahadewa; Made Gemma Daniswara Maliawan (Acta Neurologica Taiwanica)
Purpose: Secondary (TN) caused by an arachnoid cyst in the (CPA) region is a rare finding. Based on the reported literature, there are only 5 cases of secondary trigeminal neuralgia caused by an arachnoid cyst in the cerebellopontine angle region. Case report: A 27-year-old female presented to our neurosurgery clinic with a 2-year history of brief episodes of paroxysm pain in the left cheek. The pain was described as an electric shock-like pain triggered by simple stimuli. The magnetic resonance imaging (MRI) showed a well-confined cystic lesion in the left CPA, which compresses the left pons and the cisternal segment of the left trigeminal nerve. The patient was managed operatively to fenestrate the cyst and decompress the trigeminal nerve. The histopathological result of the cyst wall was consistent with an arachnoid cyst. Six months after surgery, the patient is in good health condition and symptom-free without medication. Conclusion: Arachnoid cyst in the CPA region is one of the rare causes of secondary TN. Preoperative imaging with MRI is important to provide better results to differentiate the pathology. Surgical treatment to fenestrate the arachnoid cyst and decompress the trigeminal nerve have a good result and can improve the patient’s quality of life.